Pengenalan Data Oseanografi - Setiawan, Agus (Jurnal Hidrosfir Indonesia, 2007)
Data, in general, can be classified into primary and secondary data. Primary data can be defined as information that has been collected at first hand, while secondary data usually refer to the information that has been collected by another people or agency. In oceanography, based on its branch, data can be divided into physical oceanography data, chemical oceanography data, marine biology data, and marine geology data. In south east Asia, observations of marine biology and physical oceanography parameters have been performed since 17th century (during the colonial period). One of the most important expeditions that give valuable contribution during this period is Snellius expedition (1929-1930). Since 1914, a comprehensive study has been conducted by Dutch Laboratorium for Zeeondersoek in the Indonesian waters such as Java Sea, South China Sea, and Malaka Strait (1914-1919) and Java Sea (1939-1941). During 1956-1957, the first Indonesian research vessel R/ V Samudera did measurements at 100 oceanographic stations from eastern part of the Indonesian waters until seawaters in the southern Java and Sunda shelf. Some of the data have been collected during those period then used by Wyrtki (at that time he was a director of Marine Science Institute Jakarta) to make monthly current circulation maps and to study current circulation pattern in the south east Asia.Keywords: Oceanography, data